A cluster of lung injury associated with home humidifier use: clinical, radiological and pathological description of a new syndrome. Issue 8 (28th January 2014) - Hong, Sang-Bum; Kim, Hwa Jung; Huh, Jin Won; Do, Kyung-Hyun; Jang, Se Jin; Song, Joon Seon; Choi, Seong-Jin; Heo, Yongju; Kim, Yong-Bum; Lim, Chae-Man; Chae, Eun Jin; Lee, Hanyi; et al.
Abstract : Background: Over a few months in the spring of 2011, a cluster of patients with severe respiratory distress were admitted to our intensive care unit (ICU). Household clustering was also observed. Extensive laboratory investigations failed to detect an infectious cause. Methods: Clinical, radiological and pathological investigations were conducted and the Korean Center for Disease Control performed epidemiological studies. Results: The case series consisted of 17 patients. Their median age was 35 (range 28–49) years. Six were pregnant at presentation and four had given birth 2 weeks previously. All presented with cough and dyspnoea. In the majority of patients (14/17), multifocal areas of patchy consolidation were identified in the lower lung zones on the initial CT. As the condition progressed, the patchy consolidation disappeared (10/13) and diffuse centrilobular ground-glass opacity nodules started to predominate and persist. Pathological specimens (11/17) showed a bronchiolocentric, temporally homogenous, acute lung injury pattern with sparing of the subpleural and peripheral alveolar areas. Ten patients required mechanical ventilation, eight of whom subsequently received extracorporeal life support. Four of the latter underwent lung transplantation. Five of the six patients in the ICU who did not receive lung transplantation died. An epidemiological investigation revealed that all patients had used humidifier disinfectants in their homes. Conclusions: This case series report showed that lung injury and respiratory failure can occur as a result of inhaling humidifier disinfectants. This emphasises the need for more stringent safety regulations for potentially toxic inhalants that might be encountered in the home.